Thoracic outlet syndrome induced by extrathoracic giant lipoma: first case in the literature due to the atypical location - Kadir Baturhan Çiflik; Büşra Özdemir Çiflik (Journal of Cardiothoracic Surgery)
Abstract Introduction Lipoma is one of the most common mesenchymal tumours. It is mostly benign in character. Those whose size is > 10 centimetres are called giant lipomas. Although its incidence is low in the extrathoracic axillary region, brachial plexus, and pectoral region, it also causes thoracic outlet syndrome (TOS), especially if it compresses the neurovascular bundle at the thoracic outlet. Case presentation A 51-year-old male patient was admitted to the hospital with pain, numbness, and tingling in his left arm that started three months ago. A mass measuring approximately 10 × 10 cm was found in the left lateral thoracic wall, in the region just inferior to the axilla and along the lateral border of the scapula. When the patient was in the supine position, the mass was observed to migrate to the axillary region. When the patient leaned forward, it was observed that the mass shifted towards the upper part of the pectoral muscle. There was paraesthesia and tingling in the fingertips of the left hand, however, muscle strength was normal. Adson’s and Wright’s tests were positive. Considering the symptoms in the left upper extremity, we decided to excise the lesion. On postoperative day one, the patient stated that the pain and tingling in the left extremity had significantly decreased. We observed that neurological complaints significantly decreased, and oedema regressed in the first postoperative month. In the third postoperative month, the patient stated that he had no complications. Conclusion There is no study in the literature reporting that lipoma seen outside the extrathoracic regions mentioned causes TOS. Particularly mobile and large-sized lipomas might cause compression of the neurovascular bundle in the thoracic outlet areas by pushing the tissues. We aimed to report the first case of TOS caused by a giant lipoma located on the lateral thoracic wall, just inferior to the axilla and outside the thoracic cavity.